2002
DOI: 10.1097/00005392-200204000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Holmium: Yag Laser Endoureterotomy For Ureterointestinal Strictures

Abstract: Ho:YAG laser endoureterotomy for ureterointestinal stricture disease is a minimally invasive endourological procedure that may provide more durable results than other modalities used for endoureterotomy. The Ho:YAG laser with its ability to cut tissue precisely and provide hemostasis combined with its versatility and compatibility with flexible endoscopes is an ideal instrument for safely performing endoureterotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Laven and co-workers 10 reported 57% success rate in 14 renal units, with median follow-up of 20.5 months. Watterson et al 8 reported an initial 71% success rate on 23 patients, with 22 months mean follow-up, that decreased to a 56% after 3 years. These two publication report long-term patency rates that are lower than that reported for benign ureteral strictures in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laven and co-workers 10 reported 57% success rate in 14 renal units, with median follow-up of 20.5 months. Watterson et al 8 reported an initial 71% success rate on 23 patients, with 22 months mean follow-up, that decreased to a 56% after 3 years. These two publication report long-term patency rates that are lower than that reported for benign ureteral strictures in general.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Most of these publications include all benign ureteral strictures as a single entity, compiling a heterogeneous group of anastomotic strictures, iatrogenic surgical strictures and others. There are several reports on the efficiency of laser endoureterotomy on anastomotic strictures, either uretero-enteric or uretero-vesical, [8][9][10] but the results of Ho:YAG laser endoureterotomy in the specific setting of stone-associated strictures have not been defined. Since ureteral strictures associated with ureteral stones, especially impacted stones, might behave differently than other benign strictures this specific assessment is useful.…”
mentioning
confidence: 99%
“…Watterson et al reported the occurrence of two failures 29 months after endoureterotomy in cases involving ureteroenteric stricture, one of which required nephroureterectomy consequent to cancer recurrence. 7 They emphasized the need for a thorough repeat evaluation including antegrade contrast studies and possible ureteroscopic visualization in order to identify an appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the periodic replacement of the single J stent, all patients stated that their quality of life was not compromised. Percutaneous and endoscopic approaches were associated in different series with a 50% to 70% success rate [7][8][9].…”
Section: Resultsmentioning
confidence: 99%